Memasyarakatkan Bus Rapid Transit Trans Siginjai melalui komunitas dan media digital di Provinsi Jambi - Haryadi Haryadi; Moh. Arief Rakhman (Unri Conference Series: Community Engagement, 2019)
In 2018 Trans Siginjai officially began operations in the city of Jambi, with a route connecting Jambi City with Muaro Jambi District. Passing the length of the route is 19 Km, passing through two large campuses in Jambi Province. Making this BRT (Bus Rapid Transit) mode has a potential market among the community of student groups. Preliminary observations were made and several studies showed that the 1 year period after the operation of the BRT showed a condition that was not optimal. The solution offered from the service done is to see how actually the transport facilities owned by Jambi Province have a lot of additional potential besides being the only mass transportation on this route. The potential that can be raised by the TransTiginjai BRT is Multiple effects of education, ecology, economics. the target of service is students and the community who live in the city of Jambi. The method used is by activating the local community and optimizing the use of digital media with the main output being various multimedia content. After the activities have not been made significant changes have occurred but there has been an increase in awareness among media users who are targeted for service, namely those from students. From the academic side, this service also tries to prove that the synergy of the community, academics and authorities is able to provide a real solution for a city and the people who live in it.